2016
DOI: 10.1371/journal.pone.0167962
|View full text |Cite
|
Sign up to set email alerts
|

A CBL-Interacting Protein Kinase TaCIPK2 Confers Drought Tolerance in Transgenic Tobacco Plants through Regulating the Stomatal Movement

Abstract: In plants, the CBL-CIPK signaling pathways play key roles in the response to abiotic stresses. However, functional studies of CIPKs in the important staple crop wheat are very rare. In this study, we identified a CIPK gene from wheat, designated TaCIPK2. Expression analysis results showed that TaCIPK2 could be up-regulated in wheat leaves by polyethylene glycol, abscisic acid and H2O2 treatments. Subcellular localization analyses revealed that TaCIPK2 was present in whole wheat epidermal cells. A yeast two-hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…It was previously demonstrated that CIPKs participate in stress response through the ABA signaling pathway (Chen et al, 2012; Wang et al, 2016; Zhou et al, 2016). In the present study, BdCIPK31 increased plant sensitivity to ABA ( Figure 5 ), and accelerated ABA-mediated stomatal closure ( Figures 6C,D ).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated that CIPKs participate in stress response through the ABA signaling pathway (Chen et al, 2012; Wang et al, 2016; Zhou et al, 2016). In the present study, BdCIPK31 increased plant sensitivity to ABA ( Figure 5 ), and accelerated ABA-mediated stomatal closure ( Figures 6C,D ).…”
Section: Discussionmentioning
confidence: 99%
“…The pairs of recombinant plasmids of AD and BD were co-transformed into yeast strain AH109 following the Yeast Protocols Handbook (Takara, Dalian, China). Protein expression in yeast was confirmed by Western blots following a previous study (Wang et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The expression of the P5CS1 gene is regulated by OsCIPK1, enhancing production of proline which acts as a cryoprotectant during cold stress and as osmolyte during drought stress in rice (Abdula et al ., ). Both wheat TaCIPK2 and Stipa purpurea SpCIPK26 positively regulate the expression CAT genes, thereby negatively modulating H 2 O 2 content (Wang et al ., ; Zhou et al ., ). TaCIPK27 interacts with calcineurin B‐like (CBL) proteins and positively regulates drought tolerance (Wang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Both wheat TaCIPK2 and Stipa purpurea SpCIPK26 positively regulate the expression CAT genes, thereby negatively modulating H 2 O 2 content (Wang et al ., ; Zhou et al ., ). TaCIPK27 interacts with calcineurin B‐like (CBL) proteins and positively regulates drought tolerance (Wang et al ., ). In this study, it was found that MdCIPK22 transgenic apple plant produced more sugars and exhibited higher drought tolerance than the WT control (Figures and ).…”
Section: Discussionmentioning
confidence: 99%